Analysis of the Contribution and Effectiveness of Receiving Market Service Retributions to Regional Genuine Income in Yogyakarta City - Iwan, Iwan; Arisman, Arisman (Economic and Business Horizon, 2023)
Regional autonomy entails the rights, authorities, and responsibilities granted to autonomous regions, allowing them to oversee and manage their own government affairs and address local community interests in accordance with established laws and regulations. This research aims to identify the entities responsible for collecting market service fees and directing them to the local revenue office. The discussion is based on previous research findings. From these discussions, it becomes evident that several factors influence the contribution of market retribution collection to locally generated revenue. The research employs a descriptive qualitative analysis method to interpret various conditions and situations. Data collection includes interviews conducted at the Yogyakarta city regional revenue service and Yogyakarta city market. With this approach, it is anticipated that the contribution from market service levies to local revenue services will be realized. The research results conclude that by using market fees as one of the main sources of income, local governments can reduce their dependence on fund transfers from the central government.